A cross‐sectional study of packed lunchbox foods and their consumption by children in early childhood education and care services. Issue 4 (24th August 2020) - Pearson, Nicole; Wolfenden, Luke; Finch, Meghan; Yoong, Sze Lin; Kingsland, Melanie; Nathan, Nicole; Lecathelinais, Christophe; Wedesweiler, Taya; Kerr, Jayde; Sutherland, Rachel
Abstract: Aim: To (a) describe lunchbox foods packed and consumed by children attending early childhood education and care services; (b) compare the serves of foods packed and consumed with nutrition guideline recommendations; and (c) explore associations between parent characteristics and serves of food groups packed in lunchboxes. Methods: A cross sectional study was conducted on a sample of early childhood education and care services where parents provide food in the Hunter New England region of NSW, Australia. Lunchbox contents were assessed using photography and pre‐ and post‐meal weights. Descriptive statistics were used to describe packing and consumption of core food groups and discretionary foods. Results: Data on food packed and consumed were collected for 355 children's lunchboxes from 17 services (preschools n = 14, long day care services n = 3). Less than half (44%) of lunchboxes contained vegetables, and 54% contained at least one serve of discretionary foods. Less than 1% of lunchboxes met all setting‐specific nutrition guidelines. On average, children consumed 68% of lunchbox contents, with the lowest consumption rate being for vegetables. An association was found between parent education level and packing of discretionary foods (−0.36, P = <.01) but not for packing of fruit or vegetables. Conclusions: Lunchboxes contained an over‐representation of discretionary foods and under‐representation of vegetables, and children had a low preference for consuming vegetables compared with other food groups. Interventions to support parent packing of lunchboxes in line with nutrition guidelines and strategies to expand child preference for foods such as vegetables are warranted.